FACTOR RELATED FATIGUE IN OIL AND GAS WORKER: LITERATURE REVIEW - Pramudita, Revi Adib; Lestari, Fatma (HEARTY, 2025)
Oil and gas workers are faced with environmental conditions that are at risk of experiencing work fatigue. The perceived work fatigue has an impact on reducing the level of work concentration, if this condition is left unchecked it will increase the risk of work accidents. This research aims to determine the factors associated with work fatigue in oil and gas workers. This research aims to determine the factors associated with work fatigue in oil and gas workers. Research methods used in literature review with the PRISMA approach (preferred reporting items for systematic reviews and meta-analyses). In the journal search carried out on a database google scholar and ScienceDirect with the keywords "work fatigue” and “Oil and gas Industry Workers”. A total of 806 journals were identified, but 6 journals met the inclusion and exclusion criteria. Based on 6 journals that met the inclusion and exclusion criteria, it was found that the factors that influence work fatigue felt by workers are: work related factors (shift work, ergonomic, workload, night shift, noise, heat stress) And individual factors (sleep quality, motivation, respiratory rate, blood pressure). The impact of work fatigue felt by workers increases the risk of work accidents and reduces work productivity. It can be concluded that the factors related to work fatigue are work-related factor and individual factor.